Violência familiar, pauperismo e sociabilidade burguesa: a vida das famílias atendidas no CREAS II em Ribeirão Preto-SP - Ros, Ana Carolina Pontes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Historically domestic violence has been addressed in a focused and disjointed manner by the Social Service, from the use of theoretical and methodological frameworks and concepts that restrict the possibilities of understanding the real in its entirety. Assuming that such situations , even if mediated by the uniqueness of human beings, are led by social beings embedded in a given social organization, it is understandable that such violence occurs exploited and encouraged by this sociability, imposing social values and rules forming individuals as social individuals. Thus, it is not an isolated phenomenon, but a social one that although objectified in the family sphere, constitutes from wider and more complex mediations related to capitalist social structure. This research, sought to analyze the interfaces between the situations of domestic violence and the experience of pauperism objectified in the lives of the families involved in CREAS II Ribeirão Preto, as well as measurements and determinants that influence the forms of production and reproduction of this violence. Note that the choice of pauperism as one of the main categories of analysis, along with the category of work arose from the observation that, within this research, no reference was made to any family, but those served by Social Assistance Policy, which comprise the most impoverished parts of the working class, ie the stagnant reserve army of labor available to fluctuations and capital needs. Apart from having the historical-dialectical materialism as a theoretical reference, bibliographical research, documents and field surveys were used, crisscrossing quantitative and qualitative data. Far from exhausting this complex subject, some pointers to help you uncover the reality experienced by these families in order to provide support to the work of the social worker in this field were surveyed. Be understood that the unique situations of domestic violence seen in CREAS II have...

Historicamente a violência familiar tem sido abordada pelo Serviço Social de forma focalizada e fragmentada, a partir da utilização de referenciais teórico-metodológicos e conceitos que restringem as possibilidades de compreensão do real em sua totalidade. Partindo do pressuposto de que, tais situações, ainda que mediadas pela singularidade dos sujeitos, são protagonizadas por seres sociais inseridos numa dada organização social, entende-se que essa violência ocorre instrumentalizada e estimulada por essa sociabilidade, que impõe valores sociais e estabelece as regras que formam os indivíduos como indivíduos-sociais. Assim, não se trata de um fenômeno isolado, mas sim social que, apesar de objetivado na esfera familiar, constitui-se a partir de mediações mais amplas e complexas, relacionadas à estrutura social capitalista. Buscou-se então, por meio desta pesquisa, analisar as interfaces entre as situações de violência familiar e a vivência do pauperismo objetivado na vida das famílias atendidas no CREAS II de Ribeirão Preto, bem como as mediações e determinantes que influenciam as formas de produção e reprodução dessa violência. Cabe ressaltar que a escolha do pauperismo como uma das categorias principais de análise, ao lado da categoria trabalho, essa central nesse estudo, surgiu pela constatação de que, no espaço dessa pesquisa, não se fez referência a qualquer família, mas àquelas atendidas pela política de Assistência Social, as quais compõem as parcelas mais pauperizadas da classe trabalhadora, ou seja, o exército industrial de reserva estagnado disponível as oscilações e necessidades do capital. Tendo como referencial teórico-metodológico o materialismo histórico-dialético, foram utilizadas as pesquisas bibliográfica, documental e de campo, entrecruzando dados quantitativos e qualitativos. Longe de esgotar essa complexa temática, foram levantados...
Keywords: Sistema Único de Assistência Social (Brasil); Serviço social; Violência familiar; Bem-estar social; Serviço social com a familia - Ribeirão Preto (SP); Assistentes sociais - Prática; Assistência social - Brasil; Social service